PENERAPAN HYGIENE DI RUMAH MAKAN SALERO BUNDO ULAK KARANG PADANG - Nuraini Nuraini; Silfeni Silfeni; Kasmita Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2018)
This study aims to determine the application of hygiene in Salero Bundo Rumah Makan Padang Ulak Karang consisting of indicators Hygiene Equipment. This research is a descriptive study with qualitative data. Data was collected using interviews, observation and documentation involving informants, namely: business and employees Salero Bundo Rumah Makan. Data analysis techniques in the study include: data reduction, data presentation and conclusions. The results of this research are: 1) Integrity of equipment, inadequate, defective equipment will be replaced by the damage, broken equipment will be discarded and not used again. 2) Washing equipment, not yet qualified applies, clean up leftover food, wash the equipment and place the equipment on a table to dry. 3) Maintenance of equipment, cleaning equipment, storing equipment in the space provided, and not to stack the equipment with other equipment. 4) Storage equipment, small drawers are made of wood, the absence of adequate storage space.Keyword: Hygiene Equipment, Eating.